1986
DOI: 10.1002/j.1460-2075.1986.tb04427.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of N-linked oligosaccharide trimming mannosidases blocks human B cell development.

Abstract: Deoxymannojirimycin (dMM) or swainsonine (SW), which block conversion of high‐mannose to complex‐type N‐linked glycans, strongly inhibited the production of immunoglobulin (Ig) when added to cultures of human lymphocytes together with the polyclonal B cell activators pokeweed mitogen (PWM) and Staphylococcus aureus (SAC). To obtain the inhibitory effect, inhibitor had to be present during the first 36 h of culture. Addition at later timepoints was less effective and showed that neither inhibitor interfered wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…at 65°C in 0.1 x standard saline citrate. Biochemical analysis of Class I antigens Splenocytes from mice were radiolabeled with [35S]methionine and Class I antigens were isolated by immunoprecipitation as described for human lymphoid cells (Tulp, 1986;Neefjes et al, 1986). The following reagents were used: BBM1, an anti-human (32m Mab that does not react with heavy chain -(2m complexes (Stam et al, 1986); W6/32, an anti-HLA-A, -B, -C antibody that recognizes only fully assembled Class I molecules ; H-2, a mixture of the following mouse Mabs: F5.21.27 (mI7), 20.8.4 (m57), 28.8.6 (m61) and H142-45 (m48) specific for the H-2q and H-2b haplotypes, kindly provided by Prof.J.Klein, Tuebingen; (am-(2m, a rabbit anti mouse ,32m serum kindly provided by Dr P.Peterson, Uppsala, a reagent which reacts preferentially with free mouse 02m; normal serum from either mouse or rabbit, as indicated in the figure legend.…”
Section: Facs Analysis Ofprotein Expression On Splenocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…at 65°C in 0.1 x standard saline citrate. Biochemical analysis of Class I antigens Splenocytes from mice were radiolabeled with [35S]methionine and Class I antigens were isolated by immunoprecipitation as described for human lymphoid cells (Tulp, 1986;Neefjes et al, 1986). The following reagents were used: BBM1, an anti-human (32m Mab that does not react with heavy chain -(2m complexes (Stam et al, 1986); W6/32, an anti-HLA-A, -B, -C antibody that recognizes only fully assembled Class I molecules ; H-2, a mixture of the following mouse Mabs: F5.21.27 (mI7), 20.8.4 (m57), 28.8.6 (m61) and H142-45 (m48) specific for the H-2q and H-2b haplotypes, kindly provided by Prof.J.Klein, Tuebingen; (am-(2m, a rabbit anti mouse ,32m serum kindly provided by Dr P.Peterson, Uppsala, a reagent which reacts preferentially with free mouse 02m; normal serum from either mouse or rabbit, as indicated in the figure legend.…”
Section: Facs Analysis Ofprotein Expression On Splenocytesmentioning
confidence: 99%
“…The following reagents were used: BBM1, an anti-human (32m Mab that does not react with heavy chain -(2m complexes (Stam et al, 1986); W6/32, an anti-HLA-A, -B, -C antibody that recognizes only fully assembled Class I molecules ; H-2, a mixture of the following mouse Mabs: F5.21.27 (mI7), 20.8.4 (m57), 28.8.6 (m61) and H142-45 (m48) specific for the H-2q and H-2b haplotypes, kindly provided by Prof.J.Klein, Tuebingen; (am-(2m, a rabbit anti mouse ,32m serum kindly provided by Dr P.Peterson, Uppsala, a reagent which reacts preferentially with free mouse 02m; normal serum from either mouse or rabbit, as indicated in the figure legend. The resulting immunoprecipitates, all prepared from equal aliquots of lysate, were analyzed by lD-IEF (Tulp, 1986;Neefjes etal., 1986), either directly or after treatment with neuraminidase (NANAse) as described (Neefjes et al, 1986). Cytofluorimetric analysis of splenocytes Splenocytes were stained with h.p.l.c.-purified W6/32 antibody which had been directly conjugated with fluoresceinisothiocyanate, and analyzed in a FACS IV (Becton-Dickinson).…”
Section: Facs Analysis Ofprotein Expression On Splenocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of N-linked oligosaccharides in B cell maturation was not recognized until Tulp et al [24] reported that Ig production in a PWM-SAC-stimulated system was inhibited by both deoxymannojirimycin (dMM) and SW, inhibitors of mannosidase I and mannosidase 11, respectively. Our results were consistent with these findings, showing that SW, CSP or Nase inhibited B cell maturation in a PWM-stimulated system.…”
Section: Discussionmentioning
confidence: 99%
“…Oligosaccharides and glycan chains of glycoproteins play numerous biological roles, many of which are essential for normal cellular activities, as in cell development, 1,2) immune responses, 3,4) infection, 5,6) and malignant transformation. 7,8) All in all, however, a precise understanding of molecular basis of their functions is difficult to achieve.…”
Section: Deciphering the Roles Of Glycan Processing In Glycoprotein Qmentioning
confidence: 99%